1997
DOI: 10.1177/014107689709000107
|View full text |Cite
|
Sign up to set email alerts
|

Introducing complementary medicine into the medical curriculum

Abstract: We surveyed the deans of British medical schools to determine the provision of complementary medicine in the undergraduate curriculum. We also sampled medical students at one British medical school to determine their knowledge of, and views on instruction in, complementary medicine. There is little education in complementary medicine at British medical schools, but it is an area of active curriculum development. Students' levels of knowledge vary widely between different therapies. Most medical students would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 6 publications
5
38
0
4
Order By: Relevance
“…Thus, we hope that our study will facilitate comparisons between Studies in other countries revealed a geographical difference in the knowledge of CAM modalities among medical students. The Australian students' self-perceived knowledge of acupuncture, meditation and massage was the highest, 9 British students' knowledge of acupuncture, yoga and homeopathy were highest, 10 whilst the American students were most knowledgeable on massage, herbal medicine and meditation. 13 There were many CAM modalities which students of all four countries were found to have more knowledge of, namely acupuncture, meditation and massage.…”
Section: Knowledge Of Cammentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, we hope that our study will facilitate comparisons between Studies in other countries revealed a geographical difference in the knowledge of CAM modalities among medical students. The Australian students' self-perceived knowledge of acupuncture, meditation and massage was the highest, 9 British students' knowledge of acupuncture, yoga and homeopathy were highest, 10 whilst the American students were most knowledgeable on massage, herbal medicine and meditation. 13 There were many CAM modalities which students of all four countries were found to have more knowledge of, namely acupuncture, meditation and massage.…”
Section: Knowledge Of Cammentioning
confidence: 92%
“…8 The Traditional and Complementary Medicine Branch of the Ministry of Health, Singapore regulates TCM practitioners, implements tight control of Chinese medicinal materials and establishes baseline information on the status of various forms of CAM in Singapore. 8 Surveys conducted in Australia, 9 Europe, [10][11][12] North America, [13][14][15][16][17] and the Middle East, [18][19][20] have shown that medical students have a high level of interest in and positive attitudes toward CAM. In contrast, few such studies come from East Asia where traditional oriental medicine is widely practised.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Rampes et al 24 , a maioria das escolas médicas não provê educação formal sobre terapias complementares. Como resultado da ausência destas terapias nas escolas médicas, a mídia e as experiências familiares surgem como as principais formas de obtenção de conhecimento 10,12,23 .…”
Section: Discussionunclassified
“…Tais resultados corroboram a tendência, já evidenciada por outros estudos 3,8 , de um crescente interesse e aceitação dessa prática complementar no âmbito das escolas médicas. No entanto, a presença do ensino de acupuntura nas escolas mé-dicas brasileiras é discreta e não atende satisfatoriamente à demanda dos graduandos 11 , que a veem como uma disciplina importante em sua formação profissional e são bastante favoráveis à sua inclusão no currículo [12][13][14] .…”
Section: Discussãounclassified